The distinctive signature of regulatory CD4 T cells committed in the human thymus - Raposo, Alexandre A. S. F.; Paço, Susana; Ângelo-Dias, Miguel; Rosmaninho, Pedro; Almeida, Afonso R. M.; Sousa, Ana E. (Frontiers in Immunology, 2025)
Thymically committed regulatory CD4 T cells (tTregs) are essential for immune homeostasis and self-tolerance. We established the human tTreg Expression Signature by comparing genome-wide transcriptomic profiles between tTregs and their conventional counterparts (tTconvs). We further exploited the high sequencing depth of our bulk RNA-seq data to identify a subset of 250 genes significantly expressed in human tTregs and with neglectable expression in tTconvs, defined as below the levels of expression of IL2RA, that we named thymic Treg “private” genes. Notably, pathways related to cell motility, inflammation, and T-cell effector specification were overrepresented within the tTreg private genes. We found that 163 of these genes were significantly less expressed in circulating naïve and memory Tregs when compared to peripheral data generated in parallel. This result suggested a higher activity for most of the “private” genes in the thymus when compared to the peripheral compartments. Altogether, we provide a unique resource to inform future studies, such as for improving annotation in single-cell and spatial transcriptional data, or help in designing human studies to validate putative biomarkers for thymically committed Tregs, a priority in the field.